Oscillatory Tip Leakage Flows and Stability Enhancement in Axial Compressors - Feng Lin; Jingyi Chen (International Journal of Rotating Machinery, 2018)
Rotating stall axial compressor is a difficult research field full of controversy. Over the recent decades, the unsteady tip leakage flows had been discovered and confirmed by several research groups independently. This paper summarizes the research experience on unsteady tip leakage flows and stability enhancement in axial flow compressors. The goal is to provide theoretical bases to design casing treatments and tip air injection for stall margin extension of axial compressor. The research efforts cover (1) the tip flow structure at near stall that can explain why the tip leakage flows go unsteady and (2) the computational and experimental evidences that demonstrate the axial momentum playing an important role in unsteady tip leakage flow. It was found that one of the necessary conditions for tip leakage flow to become unsteady is that a portion of the leakage flow impinges onto the pressure side of the neighboring blade near the leading edge. The impediment of the tip leakage flow against the main incoming flow can be measured by the axial momentum balance within the tip range. With the help of the theoretical progress, the applications are extended to various casing treatments and tip air recirculation.